2020
DOI: 10.1007/s00296-020-04511-w
|View full text |Cite
|
Sign up to set email alerts
|

The semi-automated algorithm for the detection of bone marrow oedema lesions in patients with axial spondyloarthritis

Abstract: The aim of the study was to create the efficient tool for semi-automated detection of bone marrow oedema lesions in patients with axial spondyloarthritis (axSpA). MRI examinations of 22 sacroiliac joints of patients with confirmed axSpA-related sacroiliitis (median SPARCC score: 14 points) were included into the study. Design of our algorithm is based on Maksymowych et al. evaluation method and consists of the following steps: manual segmentation of bones (T1W sequence), automated detection of reference signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Several previous studies have also investigated the use of threshold-based methods for quantifying inflammation [ 23 , 24 ]. However, these studies relied on manual segmentation to identify an optimal threshold, whereas our data suggest that using manual segmentation as a “gold standard” is problematic and may lead to inconsistent interpretation especially in cases when inflammation is subtle or precise lesion boundary cannot be identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have also investigated the use of threshold-based methods for quantifying inflammation [ 23 , 24 ]. However, these studies relied on manual segmentation to identify an optimal threshold, whereas our data suggest that using manual segmentation as a “gold standard” is problematic and may lead to inconsistent interpretation especially in cases when inflammation is subtle or precise lesion boundary cannot be identified.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies relied on manual segmentation to identify an optimal threshold, whereas our data suggest that using manual segmentation as a “gold standard” is problematic and may lead to inconsistent interpretation especially in cases when inflammation is subtle or precise lesion boundary cannot be identified. To highlight this point, a recent study aiming to demonstrate the feasibility of fully-automated segmentation of BME [ 25 ] revised the threshold value developed in earlier work [ 23 ], finding an optimal threshold of 1 compared to 1.5 in the prior study. Clearly, a threshold which depends on reference standard provided by human observers is not desirable.…”
Section: Discussionmentioning
confidence: 99%
“…For example, recall and precision in the HEALTHY population were low because of low pretest probability or alternatively because of potential dissimilar aspects of BME not caused by inflammation. Earlier studies that used more balanced or predominant positive data sets reported higher recall and accuracy, suggesting that performance improves with increasing pretest probability 11,12,14 . Translated to clinical practice, the most beneficial application of these prediction models would be in patients with high suspicion or known diagnosis of SpA.…”
Section: Discussionmentioning
confidence: 99%
“…Former studies elaborated on classification of SI joint MRI on a patient level (ie, binary outcome, sacroiliitis yes/no) or image level (ie, signs of sacroiliitis on individual MRI slices) but often required manual segmentation or annotation of the region of interest (ROI). Techniques offering a more detailed (ie, quadrant‐level) prediction of inflammatory lesions are scarce 14 . This work, therefore, aimed to develop and validate a fully automated ML algorithm to predict BME along the SI joints, suggestive of inflammation, on a quadrant level in patients with SpA and controls.…”
Section: Introductionmentioning
confidence: 99%
“…From the data set of 553 single-channel MRI slices 391 images were randomly assigned to a training subset while the remaining 162 images were assigned to the testing subset. Further details concerning the data set can be found in [10].…”
Section: A Materialsmentioning
confidence: 99%